Appraisal of wellness-lifestyle status among Malaysian undergraduate students: A cross-sectional and gender-based wellness survey - Rabiu Muazu Musa, Jessica A. P. Kannan, Ummi Kalsum Wan Nek, Nur Wahyu Fatihah Md Rashid, Auni Mardhiah Ali, Nur Ain Syazwani Abdul Rashid (Journal of Applied Pharmaceutical Science, 2020)
Wellness is a continuous and intentional attempt to remain healthy and attain a maximum potential for well-being. A high level of wellness is vital to produce a well-balanced and competent graduate. This study aims at evaluating the wellness status of Malaysian undergraduate students. A total of 250 undergraduate students drawn from various faculties in one of the public universities in Malaysia participated in this study from 2019 to 2020. The wellness-lifestyle inventory that evaluates an initial rating of a person’s present attempt to remain healthy was used as a tool for assessing the wellness status of the students. Analysis for the rating scores in their awareness revealed that the students have an excellent to moderate awareness on key wellness elements consisting of avoiding chemical dependency, personal safety, emotional well-being, environmental health and protection, stress management, personal hygiene, and disease prevention, while poor scores were recorded in nutrition and health-related fitness. With reference to gender, it was observed that female students were significantly more informed in the four major areas of wellness elements, specifically health-related fitness, personal hygiene and health, disease prevention, and environmental health protection, while male students were better at avoiding chemical dependency (p < 0.05). The findings of this study provide significant information on the wellness-lifestyle status of the students and its practices that could assist the stakeholders to be informed about the students’ overall wellness, in order to be able to design appropriate activities and programs to cater to their needs.
Keywords: Wellness status, undergraduate students, healthy lifestyle, Malaysian students.